Fatores demográficos e não demográficos associados à responsabilidade dos domicílios no Brasil - Thiago Cordeiro Almeida (2023)
How the information about the person responsible for the household in Brazil is collected makes its use imprecise, because there is no clear criterion for defining the member of the household unit to whom this reference position will be attributed. Consequently, indicators that use household responsibility (or headship) rates may suffer from inaccuracies intrinsic to the changes that occur over time in the factors associated with this position. Therefore, this work seeks to analyze the profile of the people most likely to be identified as responsible for the household and verify how changes in the population, as well as in the way the question is asked, have affected this profile over time. Data from the Brazilian Demographic Census between 1970 and 2010 are used, and as a methodological strategy, it is applied descriptive analyses, binary logistic regression models for each year, and a parametric decomposition method for central tendency measures adapted to generalized linear models, to capture changes between periods. As a result, it is observed that the profile of the people identified as responsible is directly associated with the life cycle of household members and the position of financial centrality in the unit. However, this profile has become more heterogeneous over time. Associated with this heterogeneity, changes in the composition of the population appear to be predominant, with demographic characteristics gaining greater importance in recent periods. Therefore, it is crucial to evaluate alternatives for optimizing collection instruments related to this issue. In the absence of changes in the form of collection, estimates that are based on characteristics of the person of reference in the household must consider the changes that have occurred in the identification of this person who anchors all other information.